2012
DOI: 10.2460/javma.241.9.1194
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological features in dogs with peripheral nerve sheath tumors: 51 cases (1993–2010)

Abstract: Results suggested that electrophysiological studies may be sensitive for the detection of PNST and helpful in the imaging diagnosis. Epaxial electromyographic abnormalities appeared to be predictive for intervertebral or vertebral canal invasion by PNSTs in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…According to previous surveys, male predominance (71.4% and 58.8%) was reported in two studies [2,12] and female predominance was described in one study [5]. Interestingly, three female cases around mammary glands in this study were confirmed as malignant PNST.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…According to previous surveys, male predominance (71.4% and 58.8%) was reported in two studies [2,12] and female predominance was described in one study [5]. Interestingly, three female cases around mammary glands in this study were confirmed as malignant PNST.…”
Section: Discussionsupporting
confidence: 59%
“…Of the 51 PNSTs reported previously in dogs, the limb affected was thoracic in 40 dogs and pelvic in 11 dogs [12]. In contrast, the prevalence of PNSTs in hindlimb was two times higher than those in forelimb in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Motor nerve conduction velocity (MNCV) testing is valuable in the detection of neuromuscular diseases: inherited and acquired polyneuropathies (Shelton et al 2003;Gabriel et al 2006;Vanhaesebrouck et al 2008), general weakness (Jeffery et al 2006), botulism (Uriarte et al 2010), neuromuscular junction disorders (Meriggioli and Sanders 2005), polyradiculoneuritis (Hirschvogel et al 2012), cauda equina syndrome (Sekiguchi et al 2008), or peripheral nerves tumours (Le Chevoir 2012). Conduction velocity is defined as the speed at which an action potential propagates along a nerve.…”
mentioning
confidence: 99%
“…EMG recordings were taken in the corresponding muscles of the left (unaffected) forelimbs. Spontaneous electrical activity following denervation was quantified using a subjective scale: 0 = electrically silent muscle; + = rare spontaneous activity recorded at few sites; ++ = diffuse occasional spontaneous activity or frequent spontaneous activity recorded at few sites; and +++ = diffuse abundant spontaneous activity in the muscle. The level of spontaneous activity was variable.…”
Section: Clinical Reportmentioning
confidence: 99%